The synthesis and the antioxidant activity of 1-phenoxymethyl-4-aryl-5,6,7,8-tetrahydro-2a,4a,8a-triazacyclopenta[cd]azulene-3-carboxylic (or carbothionic) acid derivatives - Sergii Demchenko; Hanna Yeromina; Yulia Fedchenkova; Zinaida Ieromina; Vitaliy Yaremenko; Olha Vislous; Lina Perekhoda; Anatolii Demchenko (Pensoft Publishers, 2021)
New 1-phenoxymethyl-4-aryl-5,6,7,8-tetrahydro-2а,4a,8a-triazacyclopenta[cd]azulene-3-carboxylic (or carbothionic) acid derivatives have been designed, synthesized and evaluated for their in vitro antioxidant activity under conditions of the artificial oxidative stress using ionol, ascorbic acid and α-tocopherol as the reference drugs. It has been found that 1-phenoxymethyl-4-aryl-5,6,7,8-tetrahydro-2а,4a,8a-triazacyclopenta[cd]azulene-3-carbothionic acid derivatives 9b, 9c, 9d, 9e, 9f, 9i and 1-phenoxymethyl-4-(41-chlorophenyl)-5,6,7,8-tetrahydro-2,2a,8-triazacyclopenta[cd]azulene-3-carboxylic acid phenylamide 10 reveal a high antioxidant activity and a good in silico pharmacokinetic profile. The data obtained allowed us to select the most promising objects from the substances synthesized for further pharmacological screening for the presence of the antioxidant activity in vivo.